2012
DOI: 10.1113/expphysiol.2011.063172
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of the renal urotensin II system in the rat

Abstract: Urotensin II (UII), a peptide hormone which influences glomerular filtration rate and urine concentration, and its receptor, UT, are expressed in the adult rat kidney. The ability of the kidney to reabsorb sodium and water starts to develop in utero and matures during early postnatal life in the rat, yet little is known about the ontogeny of the renal UII system. This study mapped renal expression of the urotensin system during the fetal and postnatal periods and determined renal activity of UII in the immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…An examination of the ontogenetic pattern of UII and UTR expression in rat kidney has also revealed regional variability in UII and UTR expression from embryonic day 19 to 4 weeks after birth (Forty & Ashton 2012). However, unlike in adult, rat UII (rUII) did not alter renal hemodynamics in young (4-week-old) rats (Forty & Ashton 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An examination of the ontogenetic pattern of UII and UTR expression in rat kidney has also revealed regional variability in UII and UTR expression from embryonic day 19 to 4 weeks after birth (Forty & Ashton 2012). However, unlike in adult, rat UII (rUII) did not alter renal hemodynamics in young (4-week-old) rats (Forty & Ashton 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported recently that the urotensin system exerts a tonic influence on GFR and sodium and water excretion in 4 week-old Sprague Dawley rats [19]. Consequently, in view of the enhanced renal sensitivity to UII that we observed in adult SHR [13], we hypothesise that the urotensin system contributes to the lower GFR of the young, pre-hypertensive SHR.…”
Section: Introductionmentioning
confidence: 67%
“…anaesthetised 4-5 week-old WKY rats and SHRs were surgically prepared for renal clearance measurements [19]. A priming dose of renal clearance markers was administered via a jugular catheter (2 μCi 3 H inulin [Perkin-Elmer, Monza, Italy] and 12 mg para-aminohippuric acid [PAH] in 0.2 ml 0.154 mol/L NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies showed that elevated plasma level of UII and increased expression of UII and UT can be identified in the tissues of numerous diseased conditions, including hypertension, preeclampsia, atherosclerosis, heart failure, pulmonary hypertension, diabetes, renal failure, and various metabolic syndromes [7, 8]. It is reported that UII is upregulated in the spontaneously hypertensive rat [9], which means that UII is mainly a vasoconstrictor [9, 10]; however, recent studies also showed that UII has vasodilatory effect. An example demonstrating the dilatory function of UII is that patients on hemodialysis with lower blood pressure were found with elevated UII level [11].…”
Section: Discussionmentioning
confidence: 99%
“…Besides its constricted or dilated function on vessels, it is reported that UII has been shown to regulate epithelial sodium transport. In secretory tissues, such as opercular skin, UII inhibited active sodium and chloride transport [9]. These observations demonstrate that UII can directly affect epithelial ion transport in fish and influence body fluid homeostasis [21].…”
Section: Discussionmentioning
confidence: 99%